Bloodstream infections in the COVID-19 era: results from an Italian multi-centre study. (October 2021) - Pasquini, Zeno; Barocci, Iacopo; Brescini, Lucia; Candelaresi, Bianca; Castelletti, Sefora; Iencinella, Valentina; Mazzanti, Sara; Procaccini, Gaia; Orsetti, Elena; Pallotta, Francesco; Amadio, Giorgio; Giacometti, Andrea; et al.
Highlights: Bloodstream infections in patients with coronavirus disease 2019 (COVID-19). Secondary infection in patients with COVID-19. Spread of multi-drug-resistant pathogens among patients with COVID-19. Impact on the health system of the COVID-19 pandemic. ABSTRACT: Background: Correlation between coronavirus disease 2019 (COVID-19) and superinfections has been investigated, but remains to be fully assessed. This multi-centre study reports the impact of the pandemic on bloodstream infections (BSIs). Methods: This study included all patients with BSIs admitted to four Italian hospitals between 1 January and 30 June 2020. Clinical, demographic and microbiologic data were compared with data for patients hospitalized during the same period in 2019. Results: Among 26, 012 patients admitted between 1 January and 30 June 2020, 1182 had COVID-19. Among the patients with COVID-19, 107 BSIs were observed, with an incidence rate of 8.19 episodes per 1000 patient-days. The incidence of BSI was significantly higher in these patients compared with patients without COVID-19 (2.72/1000 patient-days) and patients admitted in 2019 (2.76/1000 patient-days). In comparison with patients without COVID-19, BSI onset in patients with COVID-19 was delayed during the course of hospitalization (16.0 vs 5 days, respectively). Thirty-day mortality among patients with COVID-19 was 40.2%, which was significantly higher compared with patients without COVID-19 (23.7%). BSIs in patients with COVID-19 were frequently caused by multi-drug-resistant pathogens, which were often centre-dependent. Conclusions: BSIs are a common secondary infection in patients with COVID-19, characterized by increased risk during hospitalization and potentially burdened with high mortality.